47, XXX syndrome with infertility, premature ovarian insufficiency, and streak ovaries - Munazzah Rafique; Solaiman AlObaid; Dania Al‐Jaroudi (Clinical Case Reports, 2019)
Abstract We report a patient with primary infertility and clinical manifestation of premature ovarian insufficiency (POI) who upon investigation was found to have streak ovaries, and genetic testing revealed Trisomy X (47, XXX). Therefore, we suggest for genetic testing in women with POI to detect common aneuploidies for better counseling and treatment.